2006
DOI: 10.1093/jnci/djj441
|View full text |Cite
|
Sign up to set email alerts
|

Endorepellin In Vivo: Targeting the Tumor Vasculature and Retarding Cancer Growth and Metabolism

Abstract: Our results provide support for the hypothesis that endorepellin is an effective antitumor vasculature agent that could be used as a therapeutic modality to combat cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
86
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 55 publications
4
86
0
1
Order By: Relevance
“…On the day tumors became visible, the mice were randomized into two groups, and one group received intraperitoneal injections of human recombinant endorepellin, whereas the other received vehicle (PBS) alone (20). Tumor sectioning and immunostains were performed as previously described (20).…”
Section: Syngeneic Tumor Xenografts and Quantification Of Tumor Angiomentioning
confidence: 99%
See 1 more Smart Citation
“…On the day tumors became visible, the mice were randomized into two groups, and one group received intraperitoneal injections of human recombinant endorepellin, whereas the other received vehicle (PBS) alone (20). Tumor sectioning and immunostains were performed as previously described (20).…”
Section: Syngeneic Tumor Xenografts and Quantification Of Tumor Angiomentioning
confidence: 99%
“…Endorepellin is a potent inhibitor in several angiogenesis assays such as endothelial cell migration, collagen-induced capillary morphogenesis, blood vessel recruitment into Matrigel plugs, and chicken chorioallontoic membrane (7,19). It also effectively retards in vivo tumor growth by specifically targeting tumor angiogenesis (20). We hypothesize that endorepellin takes effect via the LG3 domain binding to the integrin ␣2␤1 causing actin disassembly and therefore affecting three key steps of angiogenesis: endothelial cell adhesion, migration, and morphogenesis.…”
mentioning
confidence: 97%
“…In vivo studies have shown that endorepellin specifically targets the tumor vasculature and inhibits tumor angiogenesis (46). This bioactivity leads to inhibition of tumor growth without inducing apoptosis.…”
mentioning
confidence: 99%
“…Methods: Using digital autoradiography of coinjected 18 F-labeled azomycin arabinoside ( 8 F-FAZA) (assessing regional hypoxia) and a glycosylated RGD-containing peptide ( 125 I-3-iodo-DTyr 4 -cyclo(-Arg-Gly-AspDTyr-Lys(SAA)-), or 125 I-Gluco-RGD) (assessing angiogenesis via binding to avb3 integrin receptors on endothelial cells) performed on 22 EMT6 tumor xenografts, we investigated the intratumoral spatial distribution of these tracers. We applied a Bayesian bivariate image analysis using the mean tumor-tomuscle ratio as a discriminator, resulting in 4 groups: FAZA high/RGD high (Q1), FAZA low/RGD high (Q2), FAZA low/RGD low (Q3), and FAZA high/RGD low (Q4).…”
mentioning
confidence: 99%
“…Indeed, when given in combination with chemotherapy, bevacizumab, an antibody targeted against the potent angiogenic vascular endothelial growth factor, significantly increased survival in colorectal cancer patients (2). However, destroying the vasculature should severely compromise oxygen delivery and reduce the delivery of therapeutics to the solid tumor, producing or enhancing hypoxia (3), which is well known to counteract the effects of many chemotherapeutics and radiation treatment (4). Indeed, some studies have demonstrated that antiangiogenic therapy may interrupt the delivery of chemotherapeutic drugs to tumors (5) and diminish the effects of radiation therapy (6).…”
mentioning
confidence: 99%